Madrasah Riset as a Practice of Institutional Innovation: A Sociological Study of the Transformation of MAN 1 Banyumas - Lian Hidayatun; Muh Hanif (Indonesian Academy of Social and Religious Research (IASRR), 2026)
This article examines Madrasah Riset at MAN 1 Banyumas as a practice of institutional innovation in contemporary Islamic education. Rather than treating the research-madrasah program merely as a formal label or institutional branding, this study analyzes how research-oriented education is organized, routinized, and reproduced within everyday school practices. Using a qualitative fieldwork design, data were collected through interviews, non-participant observation, and documentation involving the principal, vice principal for curriculum, research teachers, and students. The data were reduced, coded, displayed, and interpreted through a sociological lens to understand the organizational transformation of the madrasah. The findings show that MAN 1 Banyumas has developed a research-based innovation ecosystem through the systematic reorganization of planning, student mapping, teacher allocation, mentoring, assessment, competition preparation, and publication of student achievements. These practices demonstrate that Madrasah Riset operates not only as a programmatic initiative but also as an institutional mechanism that shapes academic culture, teacher-student interaction, and students’ scientific habitus. The study contributes to Islamic education management, madrasah quality assurance, and research-based student development by showing how institutional innovation emerges through the alignment of policy, classroom routines, organizational communication, and mentoring practices.